Diseño de estrategias de marketing para el hostal quinara del cantón Loja provincia de Loja” - Orellana Torres, Jose Luis (2022)
The present thesis work had a general objective "To design marketing strategies for the Quinara Hostel in the canton of Loja, province of Loja" and three specific objectives, since the establishment currently has marketing problems in its services, causing a decrease in its profitability because the hostel lacks strategies that allow it to attract new customers, improve its positioning in the competitive market and thus increase its income. For the development of the research it was necessary to use the following methods: inductive, deductive and analytical, as well as research techniques such as direct observation and the application of surveys to the effective and potential demand. "To carry out the diagnosis of Hostal Quinara to know the real situation in which the company is", for the development of the first objective the analytical method was used and in this way we proceeded to analyze the macro environment of the factors: political, economic, socio-cultural, technological, ecological and legal. Then we proceeded to perform the micro environment through Porter's five forces which are the following: rivalry among competitors, customer bargaining power, bargaining power of suppliers, threat of entry of new competitors and threat of substitute products, using the research technique of direct observation during a visit to the tourist establishment, where we also conducted an internal analysis of the hostel in which we determined the infrastructure, organizational structure, business philosophy, product, price, place and distribution. Once the current situation of the company was analyzed, the F.O.D.A. matrix was made to determine the strengths, opportunities, weaknesses and threats whose aspects positively and negatively influence Hostal Quinara. "Identify the target audience to meet the current needs of the demand" for the development of the second objective was used the descriptive survey technique applied to the effective demand where the target audience was identified as the guests of the Quinara Hostel taking as reference the registration of the year 2020 in which a total population of 790 guests were registered that by applying the finite formula was determined the sample of a total of 126 people to survey containing 17 questions, The results showed the current needs that this demand requires in terms of complementary services and promotion of the hostel's services through a promotional plan that they consider should be implemented and thus meet their needs. The results of the surveys of effective demand were obtained by analyzing and interpreting the data collected through statistical tables and graphs. "Propose marketing strategies to improve the commercialization of the services of Hostal Quinara", based on all the analyzes carried out, the third objective was developed, for which the high impact matrix was used, which consists of the crossing of the variables of the SWOT matrix with the purpose of designing marketing strategies, it contains four strategic objectives that consist of their strategies, goals, indicators, activities, responsible budget, time and financing. Of which four 5 strategic objectives were developed and thus be able to improve the quality of services and increase the profitability of the hostel. Finally, the strategies that are presented will allow the proper development of each of its activities and for this it is important to raise the conclusions, which are aimed at meeting the objectives, also having the necessary recommendations to implement and execute the design of marketing strategies proposed.